2014
DOI: 10.1371/journal.pone.0089537
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Atherosclerosis among HIV-Infected Adults Attending HIV/AIDS Care at Two Large Ambulatory HIV Clinics in Uganda

Abstract: BackgroundThe increased immune activation and inflammation of chronic HIV-infection and the characteristic dyslipidemias associated with HIV infection and antiretroviral therapy (ART) contribute to an increased risk of atherosclerotic vascular disease among HIV-infected adults. There is an emerging need to understand determinants of cardiovascular disease (CVD) among individuals aging with HIV in sub-Saharan Africa. We determined the prevalence of subclinical atherosclerosis [carotid intima media thickness (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
52
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 41 publications
11
52
1
3
Order By: Relevance
“…Initially, a higher prevalence of traditional risk factors such as smoking, lipid abnormalities, and substance abuse drew a lot of attention [2931]. Initial research also focused on the effect of ART, particularly because of reported positive associations between lipid dystrophies and some ART medications [32••, 33].…”
Section: Pathogenesismentioning
confidence: 99%
“…Initially, a higher prevalence of traditional risk factors such as smoking, lipid abnormalities, and substance abuse drew a lot of attention [2931]. Initial research also focused on the effect of ART, particularly because of reported positive associations between lipid dystrophies and some ART medications [32••, 33].…”
Section: Pathogenesismentioning
confidence: 99%
“…Before the commencement of antiretroviral therapy, high blood pressures in HIV-infected subjects were frequently linked with complications including vasculopathy, renal failure and stroke (Ssinabulya et al 2014). Individual cardiovascular threat, however, is influenced by myriads of risk factors such as weight gain, drug abuse, elevated blood lipids, dyslipidemia, age, diabetes, smoking and family history (Dimala et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Before the commencement of antiretroviral therapy, high blood pressures in HIV-infected subjects were frequently linked with complications including vasculopathy, renal failure, and stroke [2]. The individual cardiovascular threat, however, is influenced by myriads of risk factors such as weight gain, drug abuse, elevated blood lipids, dyslipidemia, age, diabetes, smoking and family history [3].…”
Section: Introductionmentioning
confidence: 99%